Heat Transfer of Gas Flow within a Partially Heated or Cooled Square Cavity. (25th November 2020) - Hssikou, Mohamed; Elguennouni, Youssef; Baliti, Jamal; Alaoui, Mohammed
Abstract : Natural convection of gas flow (air) confined within an enclosed square-section cavity is investigated numerically using the lattice Boltzmann method (LBM). The right (left) side of the enclosure is partially heated (cooled) by a hot (cold) chip, while the left (right) one is completely kept at cold (hot) temperature. However, the horizontal walls and vertical parts near the chip are kept adiabatic. The buoyancy effect induced by the gravity acceleration, related to the convection force, is evaluated through the Rayleigh number in the range of 1 0 3 − 1 0 6 (laminar regime). The wall heating-ratio effect on the flow properties such as temperature and velocity profiles was examined. The heat transfer is analyzed through the Nusselt number for different chip lengths. Results show that the wall heat ratio has an interesting effect on the flow behavior. Results show good agreement with those of full natural convection in the literature, experimental, and simulation data.